The province of Shari'ah Determined - Faiz Abdullah (the other press, 2017)
this book attempts to bring clarity to the subject and determine its province. the institution of the madhhab with the doctrines of ijtihad, taqlid, and iktikaf is examined to shed greater light on the shariah as divine guidance to the ummah as well as canonical law.